Avaliação de híbridos de repolho (Brassica oleracea var. capitata) nacionais e importados - Pinheiro Reis , Waldir José; Dias Casali , Vicente Wagner; de Macedo , Álvaro Aurélio; Pinheiro Reis , Fernando (Revista Ceres, 2025)
Two new hybrids of cabbage (Brassica oleracea var. capitata), ‘H.E. 170’ and ‘H.E. 171", produced by Companhia de Sementes Agroceres S.A., were evaluated at Viçosa, Minas Gerais, Brazil. A local cultivar ‘Louco’ and the Japanese hybrids ‘Matsukaze’, ‘Natsumaki Risow’ and ‘Banchu Risow’ were used as controls.